How a Proficient Efl Learner in Senior High School Processes Writing Tasks: a Case Study - Syahril Hanafiyanto Hidayat (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates how a proficient EFL (English as a Foreign Language) student in senior high school approaches writing tasks. It highlights that while writing is a key language skill, few studies explore the specific strategies used by proficient learners. The research aims to understand these strategies to help both teachers and lessskilled students improve their writing processes. The chapter presents one main research question and five sub-questions, each targeting a specific stage of the writing process: outlining, drafting, monitoring, revising, and editing. The study is expected to contribute both practically to teaching methods and theoretically to EFL writing research. There were theories about writing tasks, especially within Indonesian senior high school settings. It explains the task-based learning (TBL) approach and outlines how writing tasks align with Indonesia’s Emancipated Curriculum, which emphasizes practical writing skills. The process approach to writing is described in detail, breaking the writing activity into five main stages. Several previous studies are discussed, but most focus on university students rather than high school learners. The chapter concludes that more research is needed on proficient high school EFL students to better understand their strategies and inform classroom practice. This study applies the qualitative case study method used in the research. The participant was a single proficient student selected from a public high school in East Java, chosen through purposive sampling based on academic performance and English skills. Data were collected through two main techniques: structured online observations of the student completing writing tasks and semi-structured interviews. The writing tasks involved two types of texts and were analyzed using Creswell’s six-step method, including coding and theme development. The researcher also validated the findings through member checking, where the participant reviewed and confirmed the accuracy of the data. The findings from this research were gained from both observations and interviews, showing how the student followed each step of the writing process. In outlining, the student mentally structured ideas and used text format and data to organize thoughts. During drafting, the student used references, wrote directly in English, and preferred to keep ideas aligned with the original outline. Monitoring was done by rereading each paragraph multiple times, listing errors, and correcting them immediately. The student revised content before grammar, avoided major topic changes, and used data to strengthen arguments, while editing focused on refining word choices, punctuation, and getting teacher feedback when needed. The findings confirmed that the proficient student followed all five writing stages and used a variety of strategies to produce high-quality texts. The study concludes that proficient students combine planning, reflection, and external support (like data and feedback) throughout the writing process. Teachers are encouraged to introduce and guide students through these steps to improve writing instruction. The study suggests that less-proficient students may benefit from learning and adapting these strategies. For future research, the chapter recommends expanding the participant group to compare strategies across different proficiency levels and school contexts.
Reupload File Repositori 4 Februari 2026_Rudy K/Lia
Keywords: Proficient Efl Learner; Writing Tasks